New universal gate library for synthesizing reversible logic circuit using genetic programming - Abubakar, M.Y. (Institute of Electrical and Electronics Engineers Inc., 2016)
We newly formed universal gate library, that includes NOT, CNOT (Feyman), Toffoli, Fredkin, Swap, Peres gates and a special gate called G gate. The gate G on its own is a universal gate, but using it alone in a library will result in large circuit realization. G gate combines the operations of Generalized Toffoli gates. For example a gate called G3 combines the operations of NOT, CNOT and T3 (3 - bit Toffoli) gates all in one place. The new library was used in synthesizing reversible circuits. The experiment was done using Genetic programming algorithm that is capable of allowing the choice of any type of gate library and optimizing the circuit. The results were promising because the gate complexity in the circuits were drastically reduced compared to previously attempted synthesis. Â© 2016 IEEE.